Incretin-responsive human pancreatic adipose tissue organoids: A functional model for fatty pancreas research - E. Lorza-Gil; O.D. Strauss; E. Ziegler; K. Kansy; M.-T. Katschke; G. Rahimi; D. Neuscheler; L. Sandforth; A. Sandforth; G. Sancar; B. Kaufmann; D. Hartmann; et al. (Molecular Metabolism)
Objective: Infiltration of adipocytes into the pancreatic parenchyma has been linked to impaired insulin secretion in individuals with increased genetic risk of T2D and prediabetic conditions. However, the study of this ectopic fat depot has been limited by the lack of suitable in vitro models. Methods: Here, we developed a novel 3D model of functionally mature human pancreatic adipose tissue organoids by aggregating human pancreatic adipose tissue-derived stromal vascular fraction (SVF) cells into organoids and differentiating them over 19 days. Results: These organoids carry biological properties of the in situ pancreatic fat, presenting levels of adipogenic markers comparable to native pancreatic adipocytes and improved lipolytic and anti-lipolytic response compared to conventional 2D cultures. The organoids harbour a small population of immune cells, mimicking in vivo adipose environment. Furthermore, they express GIPR, allowing investigation of incretin effects in pancreatic fat. In accordance, GIP and the dual GLP1R/GIPR agonist tirzepatide stimulate lipolysis but had distinct effects on the expression of proinflammatory cytokines. Conclusions: This novel adipose organoid model is a valuable tool to study the metabolic impact of incretin signalling in pancreatic adipose tissue, revealing potential therapeutic targets of incretins beyond islets. The donor-specific metabolic memory of these organoids enables examination of the pancreatic fat-islet crosstalk in a donor-related metabolic context.